2007
DOI: 10.1111/j.1651-2227.2007.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma glucose levels in healthy preschool children: effects of weight and lifestyle

Abstract: A modern lifestyle, with low levels of exercise and high-energy consumption, may explain the increasing weight and even obesity of otherwise healthy, preschool children, but does not influence their fasting plasma glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Breastfeeding and the later introduction of weaning foods have been found to contribute to faster growth during the first few months, followed by a slowing of growth and a lower BMI and in most studies also a lower length at 1 year of age (13,25,26). Breastfeeding also protects against early overweight (26), whereas smoking in pregnancy increases the risk for overweight (25–27). For the Danish children in this study, Greve also found that smoking during pregnancy and maternal and paternal overweight increased the risk of overweight at age 7.4 years, whereas children of mothers working fulltime had decreased risks if the children had earlier attended institutional day care.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding and the later introduction of weaning foods have been found to contribute to faster growth during the first few months, followed by a slowing of growth and a lower BMI and in most studies also a lower length at 1 year of age (13,25,26). Breastfeeding also protects against early overweight (26), whereas smoking in pregnancy increases the risk for overweight (25–27). For the Danish children in this study, Greve also found that smoking during pregnancy and maternal and paternal overweight increased the risk of overweight at age 7.4 years, whereas children of mothers working fulltime had decreased risks if the children had earlier attended institutional day care.…”
Section: Discussionmentioning
confidence: 99%
“…3A, p < 0.001). More moderate reductions in blood glucose levels to 4 m m (approximately 40%), which represent a plausible fasting level (Ludvigsson et al., 2007), also significantly increased the frequency of SWDs by approximately twofold in these mice (Fig. 3B, p < 0.001).…”
Section: Resultsmentioning
confidence: 85%
“…All 16 studies reported that outdoor time was positively related to physical activity. Physical activity was assessed in a variety of ways in these studies including pedometer steps counts [ 28 , 29 ], accelerometer readings of total physical activity [ 30 , 31 ] and MVPA [ 31 , 32 , 33 , 34 , 35 , 36 ], parent- and self-reported leisure time physical activity [ 37 , 38 ], and observed total physical activity and MVPA [ 39 , 40 , 41 , 42 , 43 , 44 ]. The results were consistent across sexes and different age groups.…”
Section: Resultsmentioning
confidence: 99%